Synthesis, structure and spectroscopic properties of luminescent GdVO4:Dy3+ and DyVO4 particles - Jovanovic, Dragana J.; Chiappini, Andrea; Zur, Lidia; Gavrilovic, Tamara V.; Lam Tran, Thi Ngoc; Chiasera, Alessandro; Lukowiak, Anna; Smits, Krisjanis; Dramicanin, Miroslav D.; Ferrari, Maurizio (Elsevier B.V., 2018)
In this work, we focused on the syntheses, structure and spectroscopic properties of GdVO4:Dy3+ and DyVO4 (nano)particles of different sizes and shapes (spherical nanoparticles of 2 nm, 4 nm, and 20 nm in size, nanorods with a few nanometers in diameter and up to 10–20 nm in length and microparticles of 1–8 μm) obtained by four synthetic methods. The size effect on the structure, Raman active modes, and photoluminescence emission intensities was analyzed by X-ray diffraction, Raman and photoluminescence spectroscopy, scanning and transmission electron microscopy, and diffuse reflection spectroscopy. All X-ray diffraction patterns clearly indicated presence of a single tetragonal zircon-type phase; absence of impurity phases indicate that the dopant Dy3+ ions were successfully and uniformly incorporated into the GdVO4 host lattice due to the equal valence and similar ionic radii. Micro-Raman measurements support the XRD measurements and showed Raman-active modes of the REVO4 systems (RE = Gd, Dy). The difference between the two hosts in the diffuse reflectance spectra was observed and it could be attributed to more effective Gd3+ ions on the charge transfer bands and different polarization (compared to bulk material) in smaller nanoparticles. Photoluminescence spectroscopy showed several bands in the visible and near-infrared regions which can be exclusively attributed to the f–f transitions of Dy3+ ions.
Part of this research was done during visit of D.J. to IFN-CNR CSMFO Lab. and FBK Photonics Unit, Povo-Trento, Italy, in the framework of the STSM (Grant No. 38223) from the project: COST Action MP 1401 Advanced Fibre Laser and Coherent Source as tools for Society, Manufacturing and Lifescience” (2014e2018). The authors from Vinca Institute of Nuclear Sciences acknowledge the financial support of the Ministry of Education, Science and Tech-nological Development of the Republic of Serbia (Project No: 45020 and 172056). L.T.N. Tran acknowledges the scholarship of the Ministry of Education and Training, Vietnam International Education Development. T. G. acknowledges the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/215 (1.1.1.2/16/I/001).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Dysprosium doped gadolinium vanadate; Dysprosium vanadate; Raman spectroscopy; Luminescence; Near-infrared region